Antecedents and outcomes of sustainable shipping practices : the integration of stakeholder and behavioural theories - Yuen, Kum Fai (2018)
This paper analyses the drivers and outcomes of sustainable shipping practices through the lenses of stakeholder, planned behaviour, and resource dependence theories. Theoretical models were systematically developed and compared using survey data collected from 186 shipping companies. The results reveal that a shipping company’s stakeholder pressure, attitude, and behavioural control directly influence the adoption of sustainable shipping practices, and indirectly influence business performance. Furthermore, stakeholder pressure directly influences attitude, behavioural control, and business performance. This paper contributes to the integration of stakeholder and behavioural theories on sustainable practices. Strategies to improve the adoption of sustainable shipping practices are discussed.